1997
DOI: 10.1038/sj.bdj.4809434
|View full text |Cite
|
Sign up to set email alerts
|

CASES--clinical audit; scenarios for evaluation and study

Abstract: CASES, an audit and continuing education programme, evaluated aspects of current orthodontic practice and allowed orthodontists to identify areas where their practice differed from regional and national results. Evaluation of the CASES programme verified its value in audit and continuing education and the authors hope it will encourage similar projects in other disciplines too.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In this study, retention duration was measured from the "date of end of treatment/beginning of retention" till the "date of discharge/last review", where, the retention duration was found to be an average of 10 months (307 days) with 2 review appointments during this period. According to a survey carried out in the UK in 1997, the most commonly used retention period was 12 months (Clark et al 1997). In general, at present there are insufficient research data on which to base our clinical practice on retention (Littlewood et al 2006).…”
Section: Retention Regimen and Durationmentioning
confidence: 99%
“…In this study, retention duration was measured from the "date of end of treatment/beginning of retention" till the "date of discharge/last review", where, the retention duration was found to be an average of 10 months (307 days) with 2 review appointments during this period. According to a survey carried out in the UK in 1997, the most commonly used retention period was 12 months (Clark et al 1997). In general, at present there are insufficient research data on which to base our clinical practice on retention (Littlewood et al 2006).…”
Section: Retention Regimen and Durationmentioning
confidence: 99%
“…Studies conducted among orthodontists in the UK reveal that the most common retention period is 12 months 12 . This approach was corroborated by histologic studies that have shown that supracrestal periodontal fibers remain stretched and distorted for more than 7 months after cessation of active treatment, suggesting that retention therapy should last for at least 7 months 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Audit projects that have had maximum impact have often been national or regional in nature. When orthodontists, therefore, introduced audit to their discipline through the CASES project, they took a national, collaborative approach to the topic with regional emphasis (2). This approach enabled orthodontists to step outside their individual clinical microcosms and compare their own patient management with that of colleagues both regionally and nationally.…”
Section: Clinical Auditmentioning
confidence: 99%
“…Simulated records presenting the history and case records of 6 patients were circulated. Details of the 6 simulated patients are provided in a previous publication (2). Some of the cases deliberately posed important clinical dilemmas and all the cases required participants to take decisions on clinical management (7)(8)(9)(10)(11)(12).…”
Section: Content Of Casesmentioning
confidence: 99%